The hypothalamic-pituitary-adrenal axis in the perinatal period: Its relationship with major depressive disorder and early life adversity. (8th August 2020) - Jairaj, Chaitra; O'Leary, Niamh; Doolin, Kelly; Farrell, Chloe; McCarthy, Anthony; McAuliffe, Fionnuala M.; O'Grady-Walshe, Ann; Sheehan, John; O'Keane, Veronica
Abstract: Objectives: Effects of major depressive disorder and early life adversity (ELA) on the maternal HPA axis in the perinatal period were examined. Methods: Four groups of women ( n  = 127) were recruited, with the perinatal groups being compared during pregnancy (Preg) and at two months postpartum (PP) – [1] Depressed during pregnancy (Depressed-Preg/PP), [2] Prior history of depression but euthymic during pregnancy (History-Preg/PP), [3] Healthy pregnant women (Control-Preg/PP), and [4] Healthy non-pregnant women (Non-pregnant Control). Serial saliva samples were collected over the course of a day and waking and evening cortisol, total cortisol output and the cortisol awakening response were examined. Results: There were no HPA axis differences among the three groups during pregnancy. A history of ELA, regardless of comorbid depression, was associated with higher evening cortisol levels during pregnancy ( p  = 0.015). Women in the Depressed-PP group had had higher evening cortisol levels compared to the History-PP group ( p  < 0.017). Conclusions: Evening cortisol measures are a potential marker for both ELA and depression, with higher levels during pregnancy being associated with ELA and higher levels postpartum being associated with antenatal depression.